Efforts of the Regional Office the Ministry of Law and Human Rights of West Sumatera in Encougraging Trademark Registration for MSMEs (Study on Rice Milling in Baso) - Adila Permata Sari; Kartika Dewi Irianto (SEAN Institute, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Agam Regency face a significant gap in intellectual property protection, where out of 1,891 active units, only two have registered trademarks. This study aims to analyze the efforts of the Regional Office of the Ministry of Law and Human Rights (Kanwil Kemenkumham) of West Sumatra in encouraging trademark registration and to identify the specific barriers faced by rice milling businesses in Baso. This research utilizes an empirical legal method with a descriptive qualitative approach. Data were collected through in-depth interviews with government officials and business owners, as well as document studies. The results indicate that while the government has shifted its strategy towards an Intellectual Property-Based Region (KBKI) approach, these efforts have not been fully effective at the micro level. The primary barriers identified are structural, specifically